Monitoring and alerting system for home-alone elderly - Ang, Hui Ling (2019)
This report presents the design of a fall prevention system for the elderly using an Electromyography (EMG) based muscle sensor. The muscle sensor communicates with the microcontroller (Raspberry Pi) and Python programs are run to record and assess the elderly walking muscle strength. This information is used to give feedback to the elderly and send alerts to caregivers when muscle fatigue is detected. Two prototypes were discussed in this paper, one using a wired muscle sensor and another an improvement over the first, a wireless prototype using Message Queuing Telemetry Transport (MQTT) technology. In this study, experiments were also conducted to verify the relationship between a chosen flexing muscle test and walking muscle strength of the elderly. Two muscle groups were targeted in this report namely the biceps and tibialis anterior. In general, it supports a positive correlation allowing for the projection of walking muscle strength. The result suggests that the prototype can be used as an accurate assessment of the walking muscle strength of the elderly.